Improving School Management By Effectively Managing The Pedagogical Community - Muzaffar Ummatovich Kurbanov (Genius Journals, 2023)
Education can never be separated from upbringing. In the process of education, the present and tomorrow of the country, nation and people are manifested. The role of the pedagogical team of each school of the country in solving important issues in the educational system is great. The reform of schools, the implementation of effective management is primarily associated with the reform of pedagogical communities, taking their students to a new level of Education. In this article, ensuring the country's competitiveness in a changing world is achieved by organizing effective management in a school that generates significant human capital. In the field of education, each school is a separate organism, it is distinguished from the others. The article analyzes the effective management of the school pedagogical team and its main features and the role of the head of the school in the effective organization of education and upbringing
Keywords: Leadership; school; pedagogical community; educational effectiveness